Oskar and the eight blessings - Simon, Richard, 1959-; Simon, T. R., (Tanya R.); Siegel, Mark, 1967- (New York : Roaring Brook Press, 2015)
A young Jewish refugee from Nazi Germany arrives in New York City on the seventh night of Hanukkah and receives small acts of kindness while exploring the city.
School Library Journal starred, October 2015.
Booklist starred, September 2015.
Pub Weekly, September 2015.
3.4
K-3
AD570L
Keywords: Kindness -- Juvenile fiction; Refugees -- Juvenile fiction; Jews -- Juvenile fiction; Holocaust, Jewish (1939-1945) -- Juvenile fiction; Hanukkah -- Juvenile fiction; Kindness -- Fiction; Refugees -- Fiction; Jews -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; Hanukkah -- Fiction; Holocaust, 1939-1945 -- Fiction; Historical fiction